2019
DOI: 10.1111/jgh.14652
|View full text |Cite
|
Sign up to set email alerts
|

ZNF133 is associated with infliximab responsiveness in patients with inflammatory bowel diseases

Abstract: Background and Aim Infliximab has been widely prescribed for treating inflammatory bowel disease (IBD). However, the response rates to infliximab differ among patients. Therefore, we aimed to identify the genetic and clinical markers that predict infliximab response. Methods A total of 139 Korean patients with IBD who received infliximab were classified according to infliximab response as follows: (i) primary response vs nonresponse and (ii) sustained response vs loss of response. We performed an association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…30 A growing body of evidence demonstrated that testing for NUDT15 polymorphisms may be particularly advantageous in East Asian patients, given the low prevalence of toxicity-associated TPMT alleles in this population and the much higher frequency of the NUDT15 risk allele. [17][18][19][20]23,24 Therefore, prospective screening of NUDT15 variant before initiating thiopurine treatment should also be incorporated into clinical practice to minimize the occurrence of TIM. A convenient genotyping method for NUDT15 c.415C>T detection is highly useful in the implementation of pharmacogenomic testing for clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 A growing body of evidence demonstrated that testing for NUDT15 polymorphisms may be particularly advantageous in East Asian patients, given the low prevalence of toxicity-associated TPMT alleles in this population and the much higher frequency of the NUDT15 risk allele. [17][18][19][20]23,24 Therefore, prospective screening of NUDT15 variant before initiating thiopurine treatment should also be incorporated into clinical practice to minimize the occurrence of TIM. A convenient genotyping method for NUDT15 c.415C>T detection is highly useful in the implementation of pharmacogenomic testing for clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, only 3% of Asians carry TPMT genetic variants despite that Asian patients with IBD have higher incidence of TIM (15%). [17][18][19][20] In Asia, some patients with normal TPMT activity still have significant toxicity during treatment. 18,19 Thus, variability in TIM is not fully attributed to TPMT genetic polymorphism, that is, other factors are implicated in TIM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One cohort revealed a significant association between polymorphism rs1143634 in IL1β gene, the greater cytokines' levels at baseline, and decreased response in 29 CD and 18 UC cases, based on the clinical remission of IFX at week 14 115 . Also, polymorphism rs2228273 in ZNF133 was a predictor of reduced response to IFX after the initial administration 116 .…”
Section: Pharmacogenes In Inflammatory Bowel Diseasesmentioning
confidence: 95%
“… Summary of previous predictors of response to biologic agents ( Esters et al, 2002 ; Parsi et al, 2002 ; Arnott et al, 2003 ; Louis et al, 2004 ; Ferkolj et al, 2005 ; Hlavaty et al, 2007 ; Arijs et al, 2010 ; Schreiber et al, 2010 ; Kiss et al, 2011 ; Gazouli et al, 2013 ; Lee et al, 2013 ; Atreya et al, 2014 ; Billiet et al, 2015 ; Juillerat et al, 2015 ; Vande Casteele et al, 2015 ; Bek et al, 2016 ; Detrez et al, 2016 ; Ding et al, 2016 ; Zittan et al, 2016 ; Lopetuso et al, 2017 ; Nasuno et al, 2017 ; West et al, 2017 ; Boden et al, 2018 ; Gaujoux et al, 2019 ; Jung et al, 2019 ; Verstockt et al, 2019 ; Wilson et al, 2020 ; Agrawal et al, 2022 ; Bertani et al, 2022 ) …”
Section: Potential Application Of Gut Microbiota In the Biological Th...unclassified